Differentiation of petals in the Malva alcea L. populations from the region of Central and Eastern Europe - Celka, Zbigniew; Drapikowska, Maria; Ogrodowicz, Katarzyna; Shevera, Myroslav V.; Szkudlarz, Piotr (Biodiversity: Research and Conservation, 2007)
Malva alcea is a relict of old cultivation and its today’s presence is related to the remains of medieval settlements and anthropogenic habitats located in their vicinity (roadsides, roadside ditches and thickets). The article covers the results of studies on the variability of Malva alcea corolla in seventeen localities in Central and Eastern Europe, in the whole habitat spectrum of the species under study. The largest petals (length and width) were found in Germany and two Ukrainian populations. The same populations reached the biggest values with respect to two other traits: the petal length from its base to the point of incision as well as the incision depth. Analysing the relation between the petal’s length and the incision depth it has been found that the largest petal incisions can be found among specimens of population from North-East Poland, and the smallest ones in German population, Polish population from the Poznań region and two Ukrainian ones. The Principal Component Analysis (PCA) showed differentiation between specimens from particular populations. The specimens formed two groups. The first group consists of plants from Polish populations, one Ukrainian and some specimens from the second population from Ukraine. The second group is made up of specimens from localities in Germany and the last two populations from Ukraine. The cluster analysis performed on the basis of the Euclidean distance indicated two similar groups of populations. The results should be interpreted through the prism of prehistoric and medieval cultivation of Malva alcea in the vicinity of defensive strongholds and settlements, as well as ancient and contemporary spreading of the species to anthropogenic habitats.